(untitled) (Revista Apotheke, 2022)
The issue of this paper is about the construction processes involved the simulation of a scientific publication a piece of writing from an article on scientific magazine within the installation that take part of installation "Um mosaico misterioso (2015)". Through transits between The work presents some concepts of art and science the art and science field, it shows how discursive images and obsolete systematics are decontextualized through collection, manipulation and assembly procedures, to build new relationships establish new relation between reality and appearance. The reflection maps also correspondences between constructive pro cesses of scientific image and its simulation in a specific artistic context